1980/1990 – infâncias seduzidas pelos desenhos animados: implicações comportamentais sobre a formação da imagem corporal - Santos, Carla Borges de Andrade Juliano dos (2010)
Starting from the narrative of my childhood/adolescence, which took place during the decades of 1980-1990 of the 20th century, this study was set up as a place of memory, presenting it, other memories of eight subject contemporaries, which today are parents or teachers, about memories that we all have of cartoons that both seduced and show messages that mainly those relating to the construction of body image. To do this, the methodological pathway adopted, of qualitative approach, was marked in bibliographic review, autobiographical search and field research consisting of two distinct, but complementary steps: open interviews and group discussion as orientation of Oral History. That way, the work was multidisciplinary, providing contributions to the fields of education, health, physical education and communication. The results point to the recognition of toons as transmitters of ideologies, stereotypes and educational slant messages that deserve careful analysis on the part of educators (parents and teachers) before making it available for children and adolescents. Mainly their Anime (Japanese cartoon), which are displayed in large quantities actually, being unknown to educators who say they have not been seduced by them.